PENINGKATAN HASIL BELAJAR MATERI PENYAJIAN DATA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN WORDWALL DI KELAS V SDN 16 PAGAMBIRAN PADANG - Fazila Rahmi, Putri; Yarisda Ningsih; Salmaini Safitri Syam; Melva Zainil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of fifth-grade students in the data presentation topic at SDN 16 Pagambiran, Padang. The learning process was still dominated by the lecture method, resulting in limited student participation and learning outcomes that had not yet met the Minimum Learning Achievement Criteria (KKTP). This study aimed to describe the improvement of students' learning outcomes in data presentation through the implementation of the Problem Based Learning (PBL) model assisted by Wordwall. This study employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The research subjects were 21 fifth-grade students of SDN 16 Pagambiran, Padang. Data were collected through observation, learning achievement tests, and documentation, and were analyzed using qualitative and quantitative approaches. The findings revealed that the implementation of the Problem Based Learning model assisted by Wordwall improved both the quality of the learning process and students' learning outcomes. The average learning achievement score increased from 56.19 in the preliminary condition to 75.95 in Cycle I and 84.17 in Cycle II. In addition, both teacher and student activities during the learning process showed improvement and were categorized as good. Therefore, the implementation of the Problem Based Learning model assisted by Wordwall was effective in improving students' learning outcomes in the data presentation topic for fifth-grade students at SDN 16 Pagambiran, Padang.